1999
DOI: 10.1177/104973159900900505
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Family Groups: An Alternative for Reducing Disruptive Behavioral Difficulties of Urban Children

Abstract: Objective: This article presents an evaluation of a multiple family group intervention (MFG) designed to meet the mental health needs of low-income minority children and families. Method:Children participating in the MFG are compared with children demographically and clinically similar who received individual or family therapy services at an urban mental health center. Results: Of the children referred for MFG, 59% were still in service by the 16th group meeting. Of the children assigned to individual or famil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
66
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(70 citation statements)
references
References 53 publications
(56 reference statements)
3
66
0
Order By: Relevance
“…McKay, Quintana, Kim, Gonzales, and Adil (1999) have identified the following features of multiple family group models: (a) the inclusion of children, parents and a facilitator; (b) a focus on a specific problem; and (c) the facilitation of interaction processes and exchanges between-and within-families. Although multiple family groups originally targeted families with a mentally ill member, MFG models are now being used successfully with wellfunctioning families and families with children (Dennison, 1999).…”
Section: Multiple Family Groups and The Role Of Urban Parentsmentioning
confidence: 99%
See 3 more Smart Citations
“…McKay, Quintana, Kim, Gonzales, and Adil (1999) have identified the following features of multiple family group models: (a) the inclusion of children, parents and a facilitator; (b) a focus on a specific problem; and (c) the facilitation of interaction processes and exchanges between-and within-families. Although multiple family groups originally targeted families with a mentally ill member, MFG models are now being used successfully with wellfunctioning families and families with children (Dennison, 1999).…”
Section: Multiple Family Groups and The Role Of Urban Parentsmentioning
confidence: 99%
“…Although multiple family groups originally targeted families with a mentally ill member, MFG models are now being used successfully with wellfunctioning families and families with children (Dennison, 1999). More specifically, MFG programs have been developed for families facing contemporary social and urban problems, including HIV/AIDS (McKay, Baptiste, Coleman, Madison, Paikoff, & Scott, 2000), maternal substance abuse (DeVoe, Dean, Joyce, McKay, & Bronx Collaborative Board, in press), death of loved ones through homicide (Lyon et al, 1992 as cited in Dennison, 1999), and to address behavioral problems in urban children (McKay et al, 1999). Very few interventions implementing family-based (Tolan & McKay, 1996) or dyadic approaches have been evaluated although a few have described group intervention with children who have witnessed domestic violence (e.g., Rabenstein & Lehmann, 2000;Wagar & Rodway, 1995).…”
Section: Multiple Family Groups and The Role Of Urban Parentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Of 25 reviewed studies, 16 reported on interventions that utilized a group modality, and two reported on classroom-based interventions. Numerous outcome studies of interventions delivered to groups of participants were published in the past several years (see, e.g., Auslander, Haire-Joshu, Houston, Williams, & Krebill, 2000;McKay, Gonzales, Quintana, Kim, & Abdul-Adil, 1999;Mitchell, 1999;Pomeroy, Kiam, & Abel, 1999;Rice, 2001;Rotherman-Borus, Murphy, Fernandez, & Srinivasan, 1998). Children who are research participants are often clustered into schools or classrooms (Abbott et al, 1998;Spoth et al, 1998).…”
Section: Outcome Studiesmentioning
confidence: 99%